Apple Tree Cottage. - Voight, Virginia F. (New York Young Reader Press, 1949)
Set in the Philadelphia suburbs of 1842, this is a fast- moving and interesting story of 14 year old Susan and her little sister, Candace. Father was a cabinet maker in winter, but in the summer he followed his real profession, painting , and the girls traveled the roads with him in a caravan. How they found the little home of their dreams and how they stumble upon the solution of a robbery that has been puzzling the countryside is lots of fun. Theres entertainment in the description of Susans ride to Philadelphia on one of those devilish new contraptions, the railroad train, which belched forth smoke and set fire to the passengers clothes, and theres an unusual touch in her job of coloring the plates for the fashion magazine of the day, Godeys Ladys Book.
Keywords: Children Literature